Implementasi Kurikulum Merdeka Dalam Meningkatkan Mutu Pendidikan - Shinta Ledia Ledia; Betty Mauli Rosa Bustam (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The education system in Indonesia tends to place the portion of teaching larger than the portion of education, so educational activities tend to be identified with the mere process of increasing abilities, skills, and intelligence. Meanwhile, matters of forming superior personality and quality culture have not been given fundamental attention. A variety of educational issues arise as a result of this condition, which, if not appropriately addressed, may negatively impact efforts to raise educational standards. Issues with effectiveness, efficiency, and standardization of instruction are some of the factors contributing to Indonesia's generally low quality of education. This research aimed to determine how implementing an independent curriculum could raise educational standards. This study employs data analysis as a form of qualitative research method. The data collection technique is carried out by systematically tracing scientific literature in journals, articles, books, and other sources. According to the study's findings, independent curricula play a significant role in raising educational standards because they allow for an enjoyable learning environment where children are motivated to learn while teachers are given opportunities to further develop their professional skills. Keywords: curriculum, education, quality